Citation of a taxon name identifier issued by the ICN‐recognized registration repositories instead of taxon name author citation. Issue 5 (14th September 2017) - Rambold, Gerhard; Bensch, Konstanze; Kirk, Paul M.; Yao, Yi-Jian; Robert, Vincent; Sanz, Veronica; Triebel, Dagmar
Abstract: Problems with taxon name author citation in the running text of scientific articles are outlined. Particularly, the length of author names strings has significantly increased in the last decades, which could be demonstrated by analysis of names in the LIAS database. In addition, ambiguity of author name citation has increased because of variations in author name abbreviation and incomplete or incorrect citation of authors' names. It is therefore suggested that in non‐taxonomic scientific publications, author names should be replaced by taxon name identifiers as issued by registration repositories. The advantage of such approach especially in context with linked open data and semantic network challenges is described. An additional recommendation in Article 46 of the ICN with an example is suggested.